1998
DOI: 10.1097/00005373-199808000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Methylene Blue Prevents Pulmonary Injury after Intestinal Ischemia-Reperfusion

Abstract: Methylene blue attenuated lung injury after intestinal ischemia-reperfusion. Inhibition of oxygen free radicals may be the protective mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 17 publications
5
36
0
2
Order By: Relevance
“…In addition, MB has been shown effective against oxidative stress (12,13). It is also known that hepatic devascularization increases oxidative stress and lipid peroxidation parameters (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, MB has been shown effective against oxidative stress (12,13). It is also known that hepatic devascularization increases oxidative stress and lipid peroxidation parameters (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…During reperfusion, however, the accumulated hypoxanthine is transformed by the xanthine oxidase, in the presence of molecular oxygen, into free radicals of oxygen: superoxides, peroxides, and hydroxysl 6,7,8 , resulting in a systemic inflammatory process characterized by the increase in endothelial permeability to fluids, macromolecules, and inflammatory cells 6,9,10 .The deleterious effects of reperfusion surpass the effects of the actual ischemia, since the metabolic toxins accumulated during the period of ischemia will be distributed throughout other organs 1,11,12,13 . In the intestine, IR results in tissue lesion and morphological alterations, compromising the absorptive function 14 .…”
Section: Introductionmentioning
confidence: 99%
“…For the same reason this molecule was chosen in other experiments [23][24][25][26] and in the present study. On the other side, the study of Miranda et al 27 demonstrated that MB infusion had not beneficial effect on the healing of intestinal anastomoses in an experimental I/R model in rats.…”
Section: Discussionmentioning
confidence: 99%